IL-18 and IL-35 in the serum of patients with sepsis thrombocytopenia and the clinical significance - Zhu, Meirong; Rong, Xiaoqian; Li, Min; Wang, Shaoqin (Experimental and therapeutic medicine, 2020)
Expression levels of interleukin-18 (IL-18) and IL-35 in the serum of patients with sepsis and without thrombocytopenia and patients with sepsis thrombocytopenia (TCP) were detected to preliminarily investigate their clinical significance. One hundred and sixty-six patients admitted to Jinan Central Hospital Affiliated to Shandong University from July 2013 to September 2015 were retrospectively analysed. There were 96 patients with sepsis without thrombocytopenia in the sepsis group, and 70 patients with sepsis TCP in the sepsis TCP group. In the same period, 80 healthy subjects were selected as the control group. Fluorescent quantitative PCR was used for the detection the expression of mRNA levels of IL-18 and IL-35, and Enzyme-linked immunosorbent assay for the detection of the protein concentrations of IL-18 and IL-35 in the serum of peripheral blood. The correlation between IL-18, IL-35 and platelets was analyzed. There were significant differences in albumin, creatinine, total bilirubin and platelet count between the sepsis group and the sepsis TCP group (P<0.05); the expression levels of mRNA of IL-18 and IL-35 in a karyocyte in peripheral blood in the sepsis group and the sepsis TCP group were higher than those in the control group (P<0.05); the expression of mRNA of IL-18 and IL-35 in the sepsis TCP group was higher than those in the sepsis group (P<0.05). The concentration of IL-18 and IL-35 in the sepsis TCP group was higher than in the sepsis group (P<0.05); IL-18 and IL-35 were negatively correlated with platelets (r=−0.8749, −0.6228, P<0.001). There was a significant positive correlation between serum IL-18 and IL-35 in the control group, sepsis group, and sepsis TCP group (r=0.5124, 0.5718, 0.5511, P<0.001). IL-18 and IL-35 were negatively correlated with the reduced degree of platelets in patients with sepsis and are likely to play an important role in the pathogenetic process of sepsis TCP.